Description of the male, redescription of the female and new records of Odo patricius Simon, 1900 (Araneae: Zoridae) - Taucare-Rios, Andres; Brescovit, Antonio D. (Zootaxa, 2012)
The family Zoridae (F.O. Pickard-Cambridge, 1893) is currently represented by 14 genera and 79 species distributed worldwide (Platnick, 2012), of which only the genera Xenoctenus Mello-Leitão, 1938 and Odo Keyserling, 1887 are present in Americas. Xenoctenus is represented by four species, all endemic to Argentina, while Odo has, so far, a total of 27 species distributed in Central America, South America, West Indies and Australia (Platnick, 2012). The type species of Odo is O. lenis Keyserling, 1887, a specimen female described from Nicaragua. The genus Odo has never been revised and given its wide distribution and number of species, it is probably a polyphyletic genus and a complete revision is required. Also, no new material of O. lenis or O. patricius has been described since 1900.